Comprehensive genomic characterization and differential expression analysis of m6A RNA methylation regulatory proteins (writers, readers, and erasers) in Suaeda Salsa under abiotic stress condition - Yuke Ma; Huijuan Yin; Wenhui Guo; Bao Li; Yu Chen; Jingjing Zhang; Kongshu Ji; Qiong Yu (BMC Plant Biology)
Abstract Background N 6 -methyladenosine (m6A), the most abundant mRNA modification, serves as a reversible epigenetic marker plays an increasingly pivotal role in gene regulation across diverse biological processes including embryo development, cell differentiation, flowering and stress responses in plants. The dynamic regulation of m6A modification relies on a system comprised of writers, erasers, and readers, thereby highlighting the importance of these proteins in plant lifetime. However, these proteins responsible for the m6A modification remain unknown in Suaeda salsa (S. salsa), a halophyte with exceptional ecological and economic value. Results In this study, we systematically identified 22 putative m6A-related genes in S. salsa, including 6 writers, 7 readers, and 9 erasers, which were categorized into the MT-A70 (writers), YTH (readers), and ALKBH (erasers) families. Phylogenetic and structural analyses revealed distinct evolutionary trajectories among these protein families. The protein-protein interaction (PPI) network demonstrates their association with various proteins of significant functional importance. Quantitative real-time PCR (qRT-PCR) analysis revealed elevated expression levels of SsYTHDF1 and SsYTHDF4 across all tissues, suggesting their central role in m⁶A-mediated regulation. Analysis of upstream cis-regulatory elements hinted at a potential link between these genes and stress, hormones and developmental processes. Subsequent stress response experiments confirmed that their expression levels were altered in response to low temperature, ABA and salinity treatments. Conclusions The identification of m⁶A modification components in S. salsa, coupled with their molecular evolution and expression profiling, not only establishes a foundational framework for future functional characterization of m⁶A-associated proteins, but also deciphers the mechanistic role of m⁶A-mediated epigenetic regulation in S. salsa.